Legal Regulations for the Libyan Constituent Assembly for Drafting the Constitution: An Analytical Study Approach - Boukhrig, Azaddin Abubakr Ali (Al-Mukhtar Journal of Social Sciences, 2024)
The process of determining the competent authority for constitution-making and organizing its mechanisms varies from one country to another. After the February 17 revolution in 2011, the interim legislator issued the transitional constitution and defined the powers of the constituent assembly to draft the permanent constitution. However, the drafting process raised doubts and inquiries due to the lack of precision in the provisions related to the constituent assembly, such as the scope of its powers, the timeframe, and its relationship with the legislative authority. This research aims to accurately describe the constituent assembly in a legal context, clarify its mechanisms, determine the duration of the constitution's validity, and the imposed constraints. It is crucial to provide effective institutional and popular oversight, achieve performance in line with democratic requirements, and establish legal controls that ensure balanced representation and consider ethnic and cultural diversity.
Keywords: Competent authority; Constituent assembly; Democratic challenges